Efek Pemberian Latihan Hold Relax Dan Penguluran Pasif Otot Kuadrisep Terhadap Peningkatan Lingkup Gerak Fleksi Sendi Lutut Dan Penurunan Nyeri Pada Pasien Pasca Orif Karena Fraktur Femur 1/3 Bawah Dan Tibia 1/3 Atas - Yulianto Wahyono; Budi Utomo (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Fracture, Hold-Relax, stretching Passive, LGS Knee And Pain. Handling fracture is divided into three stages, namely (1) returns the position of the bone, (2) the installation of immobilization and (3) returns a function (rehabilitation). To restore the position of the bones in the anatomical shape/reduction and installation imibilisasi, generally carried out operative measures. As a result of operative measures will cause swelling and pain. The pain that there will be increased when the joints around the fracture are moved. For protection, it will automatically happen increasing muscle tension (muscle spasm). That impact will be an increase in pain and decreased range of motion/ LGS. Postoperative problems can be minimized by measures such as physiotherapy exercises. The design of the study using two group pre-test and post-test design, hold group relaxes and passive stretching every 16 subjects, each treatment dose groups of 10 repetitions, three times a series of exercises given 2 times/day for 2 consecutive days. Conclusion: (1) exercise hold relax and stretching passive muscle quadriceps effect on pain reduction and improvement LGS knee flexion, (2) the exercise hold relax effect is better than stretching exercises passive muscle quadriceps against a decrease in pain and improvement LGS knee flexion in patients with post ORIF because the third femur fractures or fractures of the tibia below the upper third.